1988
DOI: 10.1021/jm00396a032
|View full text |Cite
|
Sign up to set email alerts
|

Triazolines. 14. 1,2,3-Triazolines and triazoles. A new class of anticonvulsants. Drug design and structure-activity relationships

Abstract: Pioneering studies in our laboratories have led to the emergence of the delta 2-1,2,3-triazolines (4,5-dihydro-1H-1,2,3-triazoles) and the closely related 1H-1,2,3-triazoles as a unique family of anticonvulsant agents hitherto unknown. Unlike the traditional anticonvulsants, the dicarboximide moiety is absent from the traiazoline ring system. This paper examines the results of evaluation of several groups of 1-aryl-5-pyridyl-substituted triazolines and triazoles with particular reference to structure-activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…1,2,3-triazoles constitute a class of compounds which have attracted considerable attention in industry, agricultural and medicinal chemistry [1][2][3][4] . Owing to their importance an impressive number of work has been published on the chemistry and synthesis of 1,2,3-triazoles [5][6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Resultsmentioning
confidence: 99%
“…1,2,3-triazoles constitute a class of compounds which have attracted considerable attention in industry, agricultural and medicinal chemistry [1][2][3][4] . Owing to their importance an impressive number of work has been published on the chemistry and synthesis of 1,2,3-triazoles [5][6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Resultsmentioning
confidence: 99%
“…It may be considered as a "built-in" "heterocyclic prodrug"; the dicarboximide moiety (-CO-NH-CO-), which is an integral part of the traditional anticonvulsant drugs, (Fig. 1), is absent in the triazolines [18]. While the nonaromatic triazoline ring system [12] may behave like aliphatic azo compounds, the additional basic ring nitrogen N-1 could give rise to reaction paths not encountered in simpler systems.…”
Section: Rationale For Testing Triazolines For Anticonvulsant Activitymentioning
confidence: 99%
“…Evaluation of Hanschtype structure -activity relationships in several different groups of 1, 5-disubstituted (I-III) and 1, 4, 5-trisubstituted (IV) 1,2,3-triazolines has indicated that while the 1,5-diaryltriazolines (IA) as a group, show no pronounced anticonvulsant action [17], replacement of the 5-aryl with a heterocyclic substituent, particularly a 4-pyridyl (II) [18] or a 2-oxo-1-pyrrolidinyl (III) [19], leads to highly enhanced anticonvulsant activity (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Complexes of triazoles play a significant role in biological processes [12][13][14][15], such as anti-inflammatory, antimycobacterials [16], and anticonvulsants [17]. Metal complexes of triazoles are used to produce pharmaceutical compounds to inhibit tumor growth and cancer in mammals [18][19][20][21]. Such compounds are also used to treat viral as well as bacterial infections [22][23][24].…”
Section: Introductionmentioning
confidence: 99%